Depiction of Kubera - Temples of India Project Team (Jio Institute, 2024)
Kubera is depicted at the bottommost external shakha (vertical band) of the garbhagriha (sanctum sanctorum) entrance of the Vishnu Temple. He is depicted with two arms, standing, holding a bag of money, and there is a pot of nidhi (wealth) placed at the bottom. Kubera is also wearing a crown and jewellery.